Communication Style of Rasulullah to His Two Wives: Khadija and Aisha - Akbar, M Audha Fareza; Vebrynda, Rhafidilla (Journal of Islamic Communication and Counseling, 2022)
This research entitled Communication Style of Rasulullah to His Two Wives: Khadija and Aisha. The formulation of the problem raised in this study is how the Prophet Muhammad's communication style to his two wives, Khadija bint Khuwailid and Aisha bint Abu Bakr. The purpose of this research is to describe the Prophet's communication style to his two wives, Khadija bint Khuwailid and Aisha bint Abu Bakar. The study applied library research (qualitative research). This research used both primary data and secondary data. Data analysis was done through the descriptive analysis method. Based on the analysis, the communication style of the Prophet with his two wives, Khadija bint Khuwailid and Aisha bint Abu Bakr used a combination of dominant, dramatic, animated expressive, open, argumentative, relaxed, attentive, impression leaving, friendly, and precise. The combination of communication styles practiced by the Messenger of Allah in communicating demonstrates his skills in carrying out communication by adjusting to the situation and condition of the communication for effective message delivery.